Chicken inasal enterprises in Iloilo City an evaluation paper - Acap, Donna Lynn Rose; Asong, Angel Grace; Cadeliña, Emavel; De Los Reyes, Loise Laine (University of the Philippines in the Visayas, College of Management, 2009)
Western Visayas is known for its chicken inasal, thus the industry of chicken inasal is growing. The three known chicken inasal enterprise in Iloilo City was Mang Inasal, Andoks and Jo's Chicken Inato. There is a need for determination of the relevance and effectiveness of the existing marketing strategies of different chicken inasal enterprises in Iloilo City on their competitive advantage and customer satisfaction. Likewise the implication of it on how these enterprises easily captured agreater market share of Ilonggo diners. The study looks into the current marketing strategies of chicken inasal enterprises in specific branches that could create competitive advantage/edge over the other, and how it affects customer satisfaction. The study will provide information on how competitive advantages of these enterprises affect customer satisfaction. The results will bring to light the general trend and dynamics of competition in the inasal industry and how the key players' unique abilities and capacity to offer service addresses emerging market opportunities. Competitive advantage of the enterprise can be on their product offering, location of the business, promotional efforts and pricing strategy. The respondents will rate these four to determine their satisfaction with the enterprise marketing mix. Only six branches, out of the many of the three most popular chicken inasal enterprises in Iloilo City, will be studied. The branches of Mang Inasal, Andok's Chicken, and Jo's Chicken Inato near Jaro District and City Proper, specifically, within General Luna St., Valeria St., and Delgado St. are the focus of the study. Mang Inasal has position their enterprise in the minds of their customer clearly. Their location is accessible to their customers. Their ambience is also comfortable. The taste f their product is competing with the native taste Jo's Chicken Inato. They offer more value for the same price as their competitors. Their promotional effort is great that the customer thinks of Mang Inasal when you speak of chicken inasal.